Climate change alters breeding phenology and reproduction in a pied flycatcher population in central Spain - ZANANDREA, IRENE (2023)
reserved In birds, some of the best studied fitness-related traits are timing of breeding, clutch size, and fledgling number (Vriend et al., 2022). The annual variation of these fitness-related traits has been correlated to multiple environmental factors, including timing and availability of resources, breeding density, temperature (Sanz et al., 2003), rainfall patterns (Öberg et al., 2015) and large-scale weather indices like the NAO (North Atlantic Oscillation) index (Møller, 2002). However, the recent world is characterized by unprecedented climatic change, which influence physical and biological processes (Rosenzweig et al., 2008). One of the most manifest effect of climate change is global warming which associates with shifts in phenology, species interactions, ecosystem dynamics, extinction risks, and changes in geographical distributions across taxa (Rosenzweig et al., 2008). In this thesis, a long-term (1991–2022) individual-based data set from a population of Iberian pied flycatchers (Ficedula hypoleuca) was used to investigate how the change in temperature and in precipitation, caused by climate change, affected the population patterns. To do so, the analysis started from two different datasets, one with the breeding information of the studied population (individual-based data set) and the other with the local climate of the study area (climatic dataset). The breeding dataset is a thirty-one-year (1991-2022) individual-based dataset in which various features have been recorded yearly per every nests. This dataset contains both significant breeding dates and individual morphological characteristics. As for the climatic data, all the local climatic information was provided by the Spanish Meteorological Agency. From these premises, the target idea was to obtain a more detailed analysis for both individual patterns and population trends. The purpose of this study was twofold: firstly, to acknowledge the overall breading season trends, and secondly to recognise if and how general climatic patterns during ...